Toward developing a sustainability index for the Islamic social finance program: an empirical investigation - Robani, Anidah; Widiastuti, Tika; Prasetyo, Arie; Mawardi, Imron; Rosida, Rida; Al Mustofa, Muhammad Ubaidillah (Public Library of Science CODEN, 2022)
Several previous studies state that the Islamic Social Finance program has not fully succeeded in creating prosperity, and there are no definite measurements to show the sustainability impact of the program. Thus, a measurement is needed to analyze various aspects in achieving the success and sustainability of Islamic social finance programs. This study developed an index for performance evaluation with an emphasis on the success and sustainability of the Islamic Social Finance program. The study used the Analytical Network Process to determine and analyze priority components. Furthermore, the Multistage Weighted Index method was used to calculate the final index score. The index was built by taking into consideration various factors, stakeholders, aspects, and indicators. This study indicates that aspects of funding contribution from donors (0.22), involvement of donors in giving advice (0.99), and controlling of supervisor (0.08) are priority aspects in the success and sustainability of the program. An empirical investigation was performed on three different programs in Indonesia: A, B, and C. Program A (0.81) and C (0.80) have succeeded in improving the beneficiaries' quality of life to the level of economic resilience, although at a low level of sustainability (76-84.33). On the other hand, program B (0.73) is at the economic reinforcement and has not yet achieved sustainability. This index can be seen as a comprehensive tool for measuring the success and sustainability of the program at several levels.